Microporous And Mesoporous Material Formation Study, Properties Investigation And Catalytic Behavior In Aldol Condensation Of Heptanal And Benzaldehyde - Haruna, Abdullahi (2019)
Porous materials play a significant role in the area of catalysis, particularly in the synthesis of useful chemicals such as jasminaldehyde. The objectives of this project are to synthesize microporous and mesoporous zeolite materials as active catalysts for synthesizing jasminaldehyde via aldol condensation of benzaldehyde with heptanal. Mesoporous aluminosilicate Mobil Composite Material number 41 (MCM-41) and microporous aluminophosphite Nankai Number 2 (NKX-2) are chosen and prepared while the formation and the properties of both materials are also studied. Firstly, the formation of AlMCM-41 containing Cs+ cation (Cs-AlMCM-41) with novel hollow nanosphere morphology is investigated using various spectroscopy, microscopy and other analytical instruments. Then, the effects of isomorphous Al substitution and the addition of alkali metal hydroxides (LiOH, NaOH, KOH and CsOH) as mineralizers on the formation, morphological and surface properties of MCM-41 and NKX-2 are also investigated. The results show that many properties of the porous solids such as porosity (pore size, pore volume), surface area, morphology, particle size and surface basicity are significantly affected by the chemical incorporation of Al and the use of different types of mineralizers. Lastly, the catalytic activity of mesoporous MCM-41 and microporous NKX-2 novel catalysts are tested in aldol reaction between benzaldehyde and heptanal using microwave and non-microwave instant heatings at 120-180 °C.